2004
DOI: 10.3354/cr027009
|View full text |Cite
|
Sign up to set email alerts
|

Growing-season moisture variability in the eastern USA during the last 800 years

Abstract: An 800 yr tree-ring-based reconstruction of the Palmer Hydrological Drought Index was used to document the frequency, severity, and duration of growing-season moisture anomalies (both wet and dry events) in the southern mid-Atlantic region of the USA. The data indicate that this region has experienced significant growing-season moisture variability (interannual to multidecadal) since A.D. 1185. Conditions during the 18th century were much wetter than they are today, and the droughts that occurred during the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Growing season moisture variability in the southern portions of the mid-Atlantic region was investigated by Quiring (2004). Using 800-year tree-ring series, the Palmer Hydrological Drought Index (PHDI) was reconstructed for the period from about 1200 through the late 20th century.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing season moisture variability in the southern portions of the mid-Atlantic region was investigated by Quiring (2004). Using 800-year tree-ring series, the Palmer Hydrological Drought Index (PHDI) was reconstructed for the period from about 1200 through the late 20th century.…”
Section: Previous Researchmentioning
confidence: 99%
“…An integration of the studies above suggest that the SRB likely experienced an interval of warmth (Cronin et al, , 2005Pederson et al, 2005) and dryness (Brush, 2001;Willard et al, 2003;Pederson et al, 2005;Saenger et al, 2006) during the period from about 800 to 1200, a time synonymous with the Medieval Warm Period in northern Europe. The region experienced generally cooler conditions during the time of the Atlantic Sector Little Ice Age (1400-1700), with highly variable summer moisture conditions throughout the last four centuries (Stahle et al, 1998;Quiring, 2004).…”
Section: Previous Researchmentioning
confidence: 99%
“…More recently, they identified 14 dry/wet cycles since 1500 AD and found evidence of multidecadal droughts in the 16th and 17th centuries. Quiring (2004) also found evidence of multidecadal drought in the eastern United States during the 16th century and suggested that the droughts of 2002–2003 in the East were not unusual relative to the past 800 years.…”
Section: Proxy Recordmentioning
confidence: 96%
“…In the Mid‐Atlantic United States, growing season moisture conditions during the twentieth century were within the range of natural climate variability when compared to the tree ring record dating to 1185 [ Quiring , 2004]. A 500 year tree ring reconstruction of PDSI in southeastern New York State indicated severe droughts occurred during the 1560s, 1620s, 1680s, 1750s, 1790s, 1820s, 1870s, 1910, and early 1960s [ Lyon et al , 2005].…”
Section: Literature Reviewmentioning
confidence: 99%